Epigenome-Wide Association Study for Transgenerational Disease Sperm Epimutation Biomarkers following Ancestral Exposure to Jet Fuel Hydrocarbons - Ben Maamar, Millissia (Reprod Toxicol, 2020)
Jet fuel hydrocarbons is the generic name for aviation fuels used in gas-turbine engine powered aircraft. The Deepwater Horizon oil rig explosion created the largest environmental disaster in U.S. history, and the second largest oil spill in human history with over 800 million liters of hydrocarbons released into the Gulf of Mexico over a period of 3 months. Due to the widespread use of jet fuel hydrocarbons, this compound mixture has been recognized as the single largest chemical exposure for military personnel. Previous animal studies have demonstrated the ability of jet fuel (JP-8) exposure to promote the epigenetic transgenerational inheritance of disease susceptibility in subsequent generations. The diseases observed include late puberty, kidney, obesity and multiple disease pathologies. The current study is distinct and was designed to identify potential sperm DNA methylation biomarkers for specific transgenerational diseases. Observations show disease specific differential DNA methylation regions (DMRs) called epimutations in the transgenerational F3 generation great-grand-offspring male rats ancestrally exposed to jet fuel. The potential epigenetic DMR biomarkers were identified for late puberty, kidney, obesity, and multiple diseases, and found to be predominantly disease specific. These disease specific DMRs have associated genes that were previously shown to be linked with each of these specific diseases. Therefore, the germline (i.e. sperm) has environmentally induced ancestrally derived epimutations that have the potential to transgenerationally transmit disease susceptibilities to subsequent generations. Epigenetic biomarkers for specific diseases could be developed as medical diagnostics to facilitate clinical management of disease, and allow preventative medicine therapeutics.